2012
DOI: 10.1111/j.1365-2702.2012.04159.x
|View full text |Cite
|
Sign up to set email alerts
|

The lived experience of women victims of intimate partner violence

Abstract: Health professionals should be astute in identifying IPV victims with whom they come into contact at work. They should assess the immediate physical and emotional needs of these women, be empathetic, show acceptance, extend a helping hand and assess home safety before discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 29 publications
4
67
0
2
Order By: Relevance
“…Some authors argue that women experiencing more severe violence (involving the use of deadly objects or the fear for one's life) seek more help [91], while others, as demonstrated in our results, do not reveal any sign of the connection between the impact of severity and their help-seeking behaviour [92]. Socio-demographics (including age, education, socioeconomic, and marital status) and psychosocial health have also been shown to influence help-seeking behaviour [91,[93][94][95]. Psychosocial dysfunction associated with IPV may negatively influence a woman's help/health seeking behaviour [94].…”
Section: Help-seeking Behaviourmentioning
confidence: 99%
“…Some authors argue that women experiencing more severe violence (involving the use of deadly objects or the fear for one's life) seek more help [91], while others, as demonstrated in our results, do not reveal any sign of the connection between the impact of severity and their help-seeking behaviour [92]. Socio-demographics (including age, education, socioeconomic, and marital status) and psychosocial health have also been shown to influence help-seeking behaviour [91,[93][94][95]. Psychosocial dysfunction associated with IPV may negatively influence a woman's help/health seeking behaviour [94].…”
Section: Help-seeking Behaviourmentioning
confidence: 99%
“…The social stigma of divorce in Ghana may be particularly influential in battered women's stay/leave actions because people in Ghana generally have a more enduring attention to the self as an object of other people's attention and social evaluative scrutiny (see Adams, 2005). Similarly, research in an interdependent society of Hong Kong observed that abused women continued to stay in abusive relationships to avoid being looked down upon or socially stigmatized by others in society (Loke et al, 2012). The thought of divorce as a potential act that could incite community evaluation and condemnation appears to keep abused women in violent conjugal relationships in Ghana.…”
Section: Discussionmentioning
confidence: 95%
“…This is consistent with Rusbult and Martz's (1995) theorization that the size of investment (e.g., number of children) in a relationship could be a significant mediating factor in the leave or stay calculus of victims of partner aggression. A more recent study in Hong Kong also revealed that abused women remained trapped in abusive relationships and endured intimate partner violence for the sake of family completeness and their children (Loke et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…L'atteggiamento omertoso è soprattutto legato al timore che eventuali veritiere dichiarazioni portino ad una maggior intrusione dei servizi sanitari e sociali all'interno della propria vita privata, limitandone la privacy (9).…”
Section: Introductionunclassified